Integrating Multidimensional Sustainability Assessment into Decisions and Policies for Promoting Sustainable Farming in India - Kumar, Shalander; Soumitra, Pramanik; Garg, Kaushal; Anantha, kanugod H.; Singh, Ramesh; Jat, Mangi L. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The study explores integrating a multidimensional sustainability framework to promote sustainable farming practices in India, focusing on the diverse agroecological zones of Latur and Solapur in Maharashtra. These two districts, chosen for their differing climatic and socio-economic conditions, showcase unique agricultural practices and resource use. Latur leans toward traditional farming with cash crops like soybean and sugarcane, while Solapur embraces a more diverse cropping pattern that includes horticulture and floriculture, with crops like guava, grapes, and chrysanthemums. The study’s careful approach, including stratified sampling and household categorization into farm household typologies, highlights its commitment to capturing the complexity of regional diversity and socio-economic challenges. The study identifies two distinct farm types in each district, differentiated by socio-economic factors such as land ownership, income, and access to irrigation. Farm Type 2 households, with larger landholdings and better resource access, tend to fare better in sustainability. In contrast, Farm Type 1 households, constrained by limited resources and lower education levels, struggle with weaker performance. This disparity underscores systemic inequities that demand targeted interventions to support the most vulnerable. Using the Multidimensional Sustainability Assessment Tool (MSAT), the study evaluates sustainability across five key areas: economic, environmental, social, human well-being, and productivity. Both districts perform reasonably well in water management and health but show major weaknesses in economic resilience and biodiversity conservation. Household-level analysis reveals more profound disparities often masked by aggregate scores, with many households falling short in income, education, and gender equity. This emphasizes the need for disaggregate level analysis and inclusive policies addressing systemic and localized issues. The study offers clear recommendations for improving the sustainability of mixed-farming systems. Localized solutions should address unique challenges in each district, such as providing better access to modern tools in Solapur and enhancing access to institutional credit in both regions. Encouraging biodiversity-friendly farming and improving gender equity can tackle systemic gaps while replicating successful practices from better-performing farm types can help uplift others. Targeted financial and educational support for marginalized households is also crucial for fostering equitable development. In conclusion, the study highlights the interconnected challenges of resource distribution, technological advancement, and socio-economic equity in Maharashtra’s farming systems. While some progress has been made, systemic vulnerabilities persist, requiring a comprehensive and multidimensional approach. The MSAT framework provides valuable insights to develop tailored strategies consisting of bundled solutions, paving the way for resilient, inclusive, and sustainable agricultural practices in India.